2018
DOI: 10.1111/pace.13340
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic versus nonthoracic MR imaging for patients with an MR nonconditional cardiac implantable electronic device

Abstract: CIED variable differences following MR scan were not dependent on the region scanned (thoracic vs nonthoracic) and there were no clinical adverse effects in this prospective cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…According to our large patient dataset and clinical experience, the MRI examinations can be performed safely on patients with CIED without limitations on pacing device type (PM/ICD/CRT-D/CRT-P), pacing device MRI compatibility (MR-conditional/MR-unsafe), patients’ pacing device dependency, or the body region scanned if the dedicated safety protocol is followed. Our finding is supported by previous studies (14,15,19,23,2527). The Heart Rhythm Society (HRS) published an expert consensus statement on MRI in patients with CIED in 2017 (28).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to our large patient dataset and clinical experience, the MRI examinations can be performed safely on patients with CIED without limitations on pacing device type (PM/ICD/CRT-D/CRT-P), pacing device MRI compatibility (MR-conditional/MR-unsafe), patients’ pacing device dependency, or the body region scanned if the dedicated safety protocol is followed. Our finding is supported by previous studies (14,15,19,23,2527). The Heart Rhythm Society (HRS) published an expert consensus statement on MRI in patients with CIED in 2017 (28).…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have demonstrated that MRI can be performed safely on patients with CIED, although some changes in device parameters have been noted (14)(15)(16)(17)(18). However, most previous studies have included limitations on patients' pacing device dependency, age of the pacing device, or body region scanned, and patients with abandoned or epicardial pacing leads have been excluded (14,15,19).…”
Section: Introductionmentioning
confidence: 99%
“…Long term effects in the form of lead dislodgement or migration of the device within the subcutaneous pocket were not noted. The safety of MRI in the recently implanted devices has been shown to be without any translational effects 90,95 and was confirmed in a retrospective evaluation of recent implants by Friedman et al 100 …”
Section: Clinical Studiesmentioning
confidence: 85%
“…Once safety was reasonably well established at the lowest strength, higher magnetic strengths were tried and were found to be well tolerated 8,67,84–93 . To keep the adverse effect of RF and gradient magnetic field at minimum most of the studies had maximum SAR of 2 W/kg (3.2 W/kg for head MRI) and slew rate of 200 T/m/s 85,92,94–96 . A few newer parameters like patient‐specific energy dose (SED) 67 (≤0.2 kJ/kg) and root mean square (RMS) of the flip angle (B1+) (B 1+RMS ) (≤2.8μT) 38 have been proposed recently but remain unvalidated for clinical use and safety.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation